ADHD AND AUTISM SPECTRUM DISORDER IN EARLY CHILDHOOD - Florina Rad; Raluca Costinescu; Iuliana Dobrescu (Amaltea Medical Publishing House, 2008)
In recent years, currently, we come to grip with "aflutter little child" which, forth somatic disorders, present also hyperactivity, inattention, and social interaction deficits and communication disorders. At this age group, currently, we find symptoms which did not fit with classical clinical features of Autism (described by Leo Kanner) neither with ADHD (Attention Deficit Hyperactivity Disorder). For these reasons appear a lot of differential diagnostic problems between ADHD and ASD (Autism Spectrum Disorder, expression used by Baron-Cohen for Pervasive Developmental Disorder), disorders with an increase of incidence in the last years. All this generate a lot of questions for nosological enframe: ADHD, TSA, ADHD co-morbid with TSA, or a new disorder? In our paper we make a review of recent epidemiology and aetiology aspects because in the last years there is an important concern for the increase of prevalence and incidence of these two disorders. We wish to emphasize that early identification and intervention allows the elaboration of some targeted therapeutically strategies, psychotherapeutic and pharmacological, adapted to each child, with increased efficiency.